2021
DOI: 10.1007/s11845-021-02795-w
|View full text |Cite
|
Sign up to set email alerts
|

Burnout on the frontline: the impact of COVID-19 on emergency department staff wellbeing

Abstract: Background Burnout is a syndrome resulting from chronic workplace stress that has not been successfully managed. Healthcare professionals are particularly susceptible to this occupational phenomenon. There is limited literature currently published addressing burnout in the context of the Irish frontline workers during the COVID-19 pandemic. Objectives Our study aims to determine the rate and degree of burnout present in the emergency department (ED) staff at St. James h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The continued pandemic has had profound effects on the health of non-COVID-19 patients (7, 71), as pandemic patients have utilized resources, caused invoking of pandemic control measures, and disrupted care throughout the entire healthcare system (7). Furthermore, there are likely lasting impacts on our healthcare system (72,73), and on those who have valiantly served during the pandemic, including mental health effects for patients and healthcare workers (72,74,75). There are high reported rates of burnout from the COVID-19 pandemic (74), particularly in frontline workers (75), which has led to attrition and further exacerbated staffing shortages (76), from which the healthcare system may never fully recover.…”
Section: Discussionmentioning
confidence: 99%
“…The continued pandemic has had profound effects on the health of non-COVID-19 patients (7, 71), as pandemic patients have utilized resources, caused invoking of pandemic control measures, and disrupted care throughout the entire healthcare system (7). Furthermore, there are likely lasting impacts on our healthcare system (72,73), and on those who have valiantly served during the pandemic, including mental health effects for patients and healthcare workers (72,74,75). There are high reported rates of burnout from the COVID-19 pandemic (74), particularly in frontline workers (75), which has led to attrition and further exacerbated staffing shortages (76), from which the healthcare system may never fully recover.…”
Section: Discussionmentioning
confidence: 99%
“…Health care workers faced increased stress, heavy workloads, longer working hours, and insufficient sleep, which were sufficient evidence of burnout ( 15 ). A study of burnout among frontline staff in emergency departments at two of Ireland's largest hospitals during COVID-19 found that nearly three quarters (74%) of staff suffered burnout ( 16 ). A large study in the United Kingdom found a significant increase in the prevalence of burnout among healthcare personnel in the context of the COVID-19 pandemic, with burnout rates at 79% ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve this, all medical and non-medical staff need to work within a cohesive network led by a leader who is able to use his or her skills to activate the potential of other members, motivating them towards the highest level of performance achievable and, at the same time, counterbalance the stress accumulated in working in such a nerve-racking environment characterised by highly variable external conditions to which the organisation, public or private, must readily adapt. Therefore, in order to contain the high level of workrelated stress generated in highly chaotic work environments such as today's healthcare sector and, at the same time, nurture worker motivation, strong leadership is essential to guide organisations that face and manage unpredictable problems (Sadeghzade et al, 2020;Ibrahim et al, 2022;Sheehan et al, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They observe that improving job content and organisational characteristics may be the key to reducing PHPs' Burnout. Sheehan et al. (2021) aimed to determine the rate and degree of Burnout among emergency department (ED) staff at St. James hospital Dublin (SJH) and Cork University Hospital (CUH), in the context of the COVID-19 pandemic.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation